Karakteristik pasien dry eye syndrome di Desa Tianyar Timur, Kecamatan Kubu, Kabupaten Karangasem - Rengga Septivianti; Anak Agung Mas Putrawati Triningrat (Universitas Udayana, 2018)
Dry eye syndrome is a multifactorial disease of tear film, which causes discomfort and visual disturbance which potentially damaged the ocular surface. Dry eye syndrome could reduce visual function, physical and social functions, which constantly and severely affect daily activities, work productivities, and quality of life. This study aims to determine the characteristics of dry eye syndrome patients in the Tianyar Village Karangasem. This is a descriptive study with cross-sectional, which applied total sampling technic, conducted in the Tianyar Village Karangasem on 24 March 2015. The number of respondents that suitable with the inclusion criteria was 42 responents. Distribution dry eye syndrome based on its characteristics, the highest number of patients was male (59.5%), in the age group 50-59 years (28.6%), and working outdoors (85.7%). Patients with history of diabetes mellitus (7.1%), history of conjunctivitis allergy (83.3%), history of smoking (28.6%), without history of coffee consumption (38.1%), with history of oral medications (23.8%), topical medication history (4.8%), and a history of eye surgery (4.8%). It can be concluded that the distribution dry eye syndrome based on its characteristic can be used to support the intervention to prevent this disease occured. Keywords: dry eye syndrome, characteristics, distribution, frequency